Oleanolic Acid Mitigates 6-Hydroxydopamine Neurotoxicity by Attenuating Intracellular ROS in PC12 Cells and Striatal Microglial Activation in Rat Brains - Msibi, Zama N. P.; Mabandla, Musa V. (Frontiers in Physiology, 2019)
Oleanolic acid (OA), a biologically active pentacyclic triterpenoid compound, has been implicated in a number of clinical benefits including antioxidant, and anti-inflammatory properties. OA has been previously shown to ameliorate the toxic effects of 6-hydroxydopamine (6-OHDA), however, the mechanism by which this effect is exhibited is not clearly understood. In the present study, we investigated the role of OA in attenuation of microglial activation in 6-OHDA induced Parkinsonian rat model. We also explored the ability of OA to attenuate 6-OHDA-induced intracellular reactive oxygen species (ROS), and thus prevent cell death in PC12 cells. We accessed the utility of immunohistochemistry to assess striatal microglial activation, where shape descriptors such as area, perimeter, Feret’s diameter, aspect ratio and solidity were determined using the Fiji ImageJ software. Intracellular ROS and cell viability were assessed in PC12 cells using the OxiSelectTM Intracellular ROS Assay Kit and MTT assay, respectively. We found that microglial activation was decreased in rats pre-treated with OA prior to 6-OHDA insult as well as in rats treated with OA 1 day post 6-OHDA exposure when compared to untreated rats, as determined by shape descriptors. This finding was in correlation with significantly improved motor symptoms and increased striatal dopamine in treated rats as compared to non-treated rats. Flow cytometry assessment of PC12 cells revealed a decreased amount of intracellular ROS in cells pre-treated with OA 6 h prior to 6-OHDA exposure and cells treated with OA 1 h post 6-OHDA exposure, suggesting that OA provides neuroprotection in PC12 cells by removing intracellular ROS, thereby reducing oxidative stress. Our finding suggest that OA exhibits its neuroprotective effect by attenuating striatal microglial activation, which results in neuroinflammation that is implicated in Parkinson’s disease pathology. Further studies detailing the mechanism by which OA interacts with microglia may be useful in understanding the role of OA in attenuating neuroinflammation.